Frequency comb offset detection using supercontinuum generation in silicon nitride waveguides - Mayer, A. S.; Klenner, A.; Johnson, A. R.; Luke, K.; Lamont, M. R. E.; Okawachi, Y.; Lipson, M.; Gaeta, A. L.; Keller, U. (Optics express, 2015)
We present the first direct carrier-envelope-offset (CEO) frequency detection of a modelocked laser based on supercontinuum generation (SCG) in a CMOS-compatible silicon nitride (Si(3)N(4)) waveguide. With a coherent supercontinuum spanning more than 1.5 octaves from visible to beyond telecommunication wavelengths, we achieve self-referencing of SESAM modelocked diode-pumped Yb:CALGO lasers using standard f-to-2f interferometry. We directly obtain without amplification strong CEO beat signals for both a 100-MHz and 1-GHz pulse repetition rate laser. High signal-to-noise ratios (SNR) of > 25 dB and even > 30 dB have been generated with only 30 pJ and 36 pJ of coupled pulse energy from the megahertz and gigahertz laser respectively. We compare these results to self-referencing using a commercial photonic crystal fiber and find that the required peak power for CEO beat detection with a comparable SNR is lowered by more than an order of magnitude when using a Si(3)N(4) waveguide.